Caste and development: Contemporary perspectives on a structure of discrimination and advantage. (October 2018) - Mosse, David
Highlights: Caste is not an archaic ritual system but a dynamic aspect of modern economies. Market-led development both weakens and reproduces caste inequalities. Caste identities and networks persist because of their advantages. Caste-based discrimination is a feature of Indian labor markets and business economy. Policy innovation adapted to the realities of caste is needed. Abstract: Inherited caste identity is an important determinant of life opportunity for a fifth of the world's population, but is not given the same significance in global development policy debates as gender, race, age, religion or other identity characteristics. This review asks why addressing caste-based inequality and discrimination does not feature in intergovernmental commitments such as the Sustainable Development Goals, and whether it should. Taking India as its focus, it finds that caste has been treated as an archaic system and source of historical disadvantage due compensation through affirmative action in ways that overlook its continuing importance as a structure of advantage and of discrimination in the modern economy, especially post-liberalization from the 1990s. A body of recent literature from anthropology, economics, history and political science is used to explore the modern life of caste in society, economy and development. Questions are asked about caste as social hierarchy, the role of caste in post-liberalization rural inequality, in urban labor markets and in the business economy, and the effect of policies of affirmative action in public-sector education and employment. Caste is found to be a complex institution, simultaneously weakened and revived by current economic and political forces; it is a contributor to persisting national socioeconomic and human capital disparities, and has major impacts on subjective wellbeing. Caste effects are not locational; they travel from the village to the city and into virtually all markets. Caste persists in the age of the market because of its advantages – its discriminations allow opportunity hoarding for others; and the threat of the advancement of subordinated groups provokes humiliating violence against them. The evidence points to the need for policy innovation to address market and non-market discrimination and to remove barriers, especially in the informal and private sector; and to ensure caste has its proper place in the global development policy debate.